Trilateral co-operation : vol, Arab Development Funds and Banks; approaches to trilateral co-operation - Traute, Scharf (Paris ; [Washington, D.C. : Development Centre of the Organisation for Economic Co-operation and Development ; sold by OECD Publications Center], 1978)
This book contains the report of OECD Development Centre established in 1975. The purpose of the report was to study the development possibilities resulting from the new situation with three decision making groups on establishment of Arab development funds, direction and future operations and measures of implementation of trilateral projects and programmes.
Bibliography: v. 1., p. 258-268.
usc 27/04/18
Loans
Keywords: Economic assistance, Arab countries